Livestock farming in the saquencipá valley, new kingdom of granada, colombia in the 16th and 17th centuries - Mora Pacheco, K. G. (Pastos, 2014)
This document brings together the results of research with the aim of analyzing the transformation of cattle ranching practices during the Colonial period in the specific context of the Saquencipá Valley on the Altiplano Cundiboyacense (High Plain) in Colombia, its relationship with land ownership and the impact that these had on the ecosystem, especially as regards soil deterioration. In order to reconstruct the farming practices used during the 16th and 17th centuries and their Iberian origins, colonial documents from the depths of the Archivo General de la Nación (Nation’s General Archive) in Bogota, Colombia and the Archivo General de Indias (General Archive of the Indies) in Seville, Spain and along with the chronicles, geographic relationships and results from the history and archeology literature were exhaustively reviewed. Taking into account factors such as the link with agriculture, the mobility and number of head of cattle, and the natural control exerted by drought and predators, the high environmental impact attributed to colonial cattle ranching in the region is questioned.